Трудно быть фотомоделью: роман / Елена Богатырева - Богатырева Елена (Огни большого города, 2001)
Экземпляры: КХ (20191126) / Инвентарный номер: 37127 / Цена: / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Б 73 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44